Analisis Kinerja Keuangan Pemerintah Daerah di Kota Jambi - Muhammad Sabyan; Andri Devita (Journal Development, 2014)
This research measures financial performance of local government (PAD) at Jambi city using ratio analysis. Local government fund must be spent based on 3 E principles that is economic, efficient, and effective. Moreover, acountability is not simply showing the ability to expend public funds, but including on how to spend economically, efficient, and effective. The result indicates the average of PAD in Jambi city is above 100%, although the regular expenses are still above PAD. Therefore, the dependence level to the central government is very high.